Safety Assessment of HEA-Enriched Cordyceps cicadae Mycelium: A Randomized Clinical Trial. (17th February 2021) - Tsai, You-Shan; Hsu, Jui-Hsia; Lin, David Pei-Cheng; Chang, Han-Hsin; Chang, Wen-Jui; Chen, Yen-Lien; Chen, Chin-Chu
Abstract: Objective: Cordyceps cicadae, a medicinal fungus, is assessed as having many functions: anti-cancer, anti-fatigue, anti-aging, immune-boosting, renal and liver protection. Since the industrial production of C. cicadae mycelium consistently manufactures bioactive compounds superior to wild fruiting bodies, there is a need to confirm the toxicity of liquid fermented C. cicadae mycelium. Studies showed the toxicity evaluation of C. cicadae mycelium in animal models, but safety reports in clinical studies are scarce. As such, a safety assessment of oral N6-(2-hydroxyethyl) adenosine (HEA-enriched) C. cicadae mycelium in humans is provided here. Method: After 49 participants ingested granules of 1.05 g of freeze-dried C. cicadae mycelium once a day for 3 months, their blood samples were collected at the beginning and end of the experiment for analysis. Results: There were no significant differences between the initial and final measurements in renal and liver function. Also, there was no influence on blood electrolytes as well as blood lipid levels. In clinical observation, there were also no side effects or adverse feelings mentioned by participants. Conclusion: These results suggested that HEA-enriched C. cicadae mycelium produced by liquid fermentation is safe and can be developed as a functional health food.